Demographics, Clinical Presentation, Staging, Management and Outcome of Urinary Bladder Cancer in Qassim Region - Badr Alharbi; Emad Alwashmi; Hatim Alnosayan; Faisal Awadh Al-Harbi; Abdullah Saleh Alayed; Munthir Mutlaq Alanazi; Faisal Abdulmajeed Almutairi; Adil Khalaf Altwairgi (International Journal of Biomedicine)
Background: Urinary bladder cancer (UBC) is one of the most common cancers worldwide. According to the 2020 Cancer Incidence Report in Saudi Arabia, there were 348 cases of UBC recorded among Saudi nationals in 2020, with 291 cases (83.62%) occurring in males and 57 cases (16.38%) in females. This study aims to assess and evaluate the prevalence, incidence, clinical symptoms, and management of UBC in the Qassim Region. Methods and Results: This retrospective study was conducted over 12 months at King Fahad Specialist Hospital in Buraidah, Saudi Arabia. The study population comprised all patients diagnosed with UBC between October 2017 and July 2024, with complete medical records, irrespective of age, gender, or nationality. Of 75 UBC patients, 81.3% were males, most participants (68.0%) were above 60, and Saudis comprised 85.3%. Hematuria was the most common symptom, reported in 57.3% alone and in 10.7% of cases with other symptoms. Most patients underwent TURBT (89.3%), while 8.0% underwent radical cystectomy. Surgical margins were negative in 96.0% of patients, and recurrence was noted in 37.3%. Histopathological analysis revealed that 97.3% of the tumors were classified as TCC. Squamous cell carcinoma and urothelial carcinoma with squamous differentiation accounted for 1.3% in each case. Most of the tumors were low-grade and non-muscle invasive. The most frequent stage was TaN0M0, reported in 44% of cases, followed by T1N0M0 at 37%. Less common stages included T1N1M0 and T2aN0M0, each accounted for 2% of the cases. Rarer stages, including TisN0M0, T2N2M0, and T3N0M0, each accounted for 1%. Conclusion: This study reports the predominance of UBC in males and older populations, with TCC as the most common histological type. Hematuria is the primary symptom, reported in more than half of the patients, indicating its critical role in early diagnosis. A significant recurrence rate necessitates rigorous surveillance post-treatment.